EFEKTIVITAS PENERAPAN KEPUTUSAN DIRJEN BIMAS ISLAM NO 379 TAHUN 2018 TENTANG BIMBINGAN PERKAWINAN DI KANTOR URUSAN AGAMA KOTA JAMBI - Rimardi Harja; Ramlah Ramlah; Rahmi Hidayati (Lafadz Jaya Publisher, 2023)
The implementation of marriage guidance for prospective bride and groom candidates at the Jambi City Religious Affairs Office is not in accordance with the Decree of the Director General of Islamic Guidance Number 379 of 2018 concerning Guidelines for Implementing Marriage Guidance for Bride and Groom Candidates. For instance, prospective bride and groom candidates do not get a marriage guidance book and the duration of the guidance is relatively short from the time stipulated by the Director General's Decree. Qualitative approach was used in this study with a research design using a case study conducted at the Jambi City Ministry of Religion Office with the research samples being the Telanaipura District Religious Affairs Office, Kota Baru District Religious Affairs Office and East Jambi Religious Affairs Office. The data was collected by using observation, interviews, and documentation. This research resulted in four things. First, the implementation of marriage guidance is divided into two: face-to-face guidance is carried out at the Jambi City Ministry of Religion office and independent guidance is carried out at the Office of Religious Affairs. Second, the inhibiting factors for the implementation of marriage guidance are internal and external factors. Third, the implementation of marriage guidance at the Jambi City Religious Affairs Office has not run optimally according to the Decree of the Director General of Islamic Guidance Number 379 of 2018. Fourth, the impact of the implementation of marriage guidance is that the bride and groom candidates receive knowledge about the implementation of marriage guidance.